Pajak Penghasilan Badan dan Dampaknya Terhadap Profitabilitas Perusahaan - Janice Leung; Jhe Giovanny Tristan; Erika Falensia; Evelline; Dina Aprillia; Tetty Sipahutar (Yayasan Literasi Emas Nusantara, 2025)
This study explores how corporate income tax influences company profitability, while also considering the roles of operating expenses and earnings management. Using a Systematic Literature Review (SLR) approach, we examined a range of empirical studies from 2017 to 2024 focused on companies listed on the Indonesia Stock Exchange. Our review shows that corporate income tax generally has a negative impact on profitability, since it directly reduces net income. Likewise, high operating costs especially when not managed efficiently tend to lower profit margins. Earnings management, although sometimes used to present a stronger financial position in the short term, can reduce the reliability of financial reports and harm profitability over time. These findings highlight the need for better cost control, responsible tax planning, and transparent financial reporting. By understanding the connection between taxes, expenses, and financial performance, companies can make more informed decisions that support both their sustainability and compliance with tax regulation.